EYL TEACHERS' STRATEGIES IN CONDUCTING SPEAKING ASSESSMENTS : A Qualitative Research in Five English Courses in Bandung - Utari, Astri Yuniar Sri (2014)
Speaking is one of the important skills in English language program. Many strategies have been introduced to help teachers in teaching the speaking skill effectively. Yet, assessing this skill is one of the difficult tasks in language learning, especially in English for Young Learners' classrooms in Indonesia. Teachers need to be competent in applying strategies to conduct a good speaking assessment. Employing qualitative methods and descriptive analyses, this study addressed the questions of what EYL teachers know about speaking assessment and what strategies they use in assessing young learners' speaking skill. The categories of speaking strategy used in this study are the ones proposed by Hughes (2003), Brown (2004) and McKay (2006). The respondents were five EYL teachers from five English Courses in Bandung. The findings based on observations and interviews showed a pattern that teaching experience and education background were in line with the number of strategies used for young learners' classrooms. The longer their experience and the higher their education level, the more strategies were used in assessing young learners' speaking skill. There were ten strategies used in assessing young learners' speaking skill. They were Question and Answer, Role-Play/Mini Dialogs, Word Repetition Tasks, Translation (of limited stretches of discourse), Picture Cued Tasks, Picture-Cued Story-Telling, Read-Aloud Tasks, Interview, Games, and Storytelling. Berbicara merupakan salah satu kemampuan yang penting dalam program pembelajaran bahasa Inggris. Banyak strategi yang telah diperkenalkan untuk membantu para guru dalam mengajarkan kemampuan berbicara secara efektif. Namun, menilai kemampuan ini adalah salah satu tugas yang cukup sulit dalam pembelajaran bahasa. Para guru dituntut untuk lebih kompeten dalam menerapkan strategi-strategi untuk melaksanakan penilaian berbicara. Menggunakan metode kualitatif dan analisis deskriptif, penelitian ini mengajukan pertanyaan-pertanyaan mengenai apa yang para guru ketahui tentang penilaian berbicara untuk anak-anak dan strategi-strategi apa yang mereka terapkan dalam menilai kemampuan berbicara anak-anak. Kategori strategi yang digunakan dalam penelitian ini merupakan strategi-strategi yang diusung oleh Hughes (2003), Brown (2004), dan McKay (2006). Para responden terdiri dari 5 orang guru bahasa Inggris yang mengajar anak-anak di 5 tempat kursus bahasa Inggris. Hasil penemuan yang berdasarkan observasi dan wawancara menunjukkan bahwa pengalaman mengajar dan latar belakang pendidikan sejalan dengan jumlah strategi yang digunakan untuk anak-anak. Lebih lamanya pengalaman dan lebih tingginya tingkat pendidikan yang dipunyai para guru, maka akan lebih banyak pula strategi yang digunakan dalam menilai kemampuan berbicara anak-anak. Terdapat 10 strategi yang digunakan dalam menilai kemampuan berbicara anak-anak. Strategi-strategi tersebut adalah Question and Answer, Role-Play/Mini Dialogs, Word Repetition Tasks, Translation (of limited stretches of discourse), Picture Cued Tasks, Picture-Cued Story-Telling, Read-Aloud Tasks, Interview, Games, dan Storytelling.